Capillary blood collection in haematology. Issue 11 (November 1974) - Stuart, J.; Barrett, B. A.; Prangnell, D. R.
Abstract : A capillary blood collection technique which facilitates the estimation of routine haematological parameters, including platelet count and sedimentation rate, is described. The technique requires 0·5 ml of blood, allows closer reproducibility than pipette collection methods, is suitable for monitoring blood counts in patients receiving cytotoxic agents, and can be integrated with semi-and fully-automated production lines.